Correlations between alterations of T-helper 17 cells and treatment efficacy after concurrent radiochemotherapy in locally advanced cervical cancer (stage IIB–IIIB): a 3-year prospective study. Issue 8 (20th April 2021) - Liu, Yi; Guo, Qiu-Fen; Chen, Jin-Long; Li, Xi-Rui; Hou, Fei; Liu, Xiao-Yan; Zhang, Wen-Jing; Zhang, Yan; Gao, Fu-Feng; Zhang, You-Zhong; Cui, Bao-Xia; Liu, Nai-Fu
Abstract: Background: Recently, T-helper 17 (Th17) cells have been proved to play an important role in promoting cervical cancer. But, till now, few study has been carried out to understand the involvement of these cells in efficacy of anti-tumor treatments. This study aimed to investigate the alterations in the percentage of circulating Th17 cells and related cytokines in locally advanced cervical cancer (LACC) patients before and after concurrent chemoradiotherapy (cCRT) and to analyze the correlations between the alterations in Th17 cells and treatment efficacy. Methods: A prospective study with 49 LACC (International federation of gynecology and obstetrics [FIGO] stage IIB–IIIB) patients and 23 controls was conducted. Patients received the same cCRT schedule and were followed up for 3 years. Circulating Th17 cells (CD3+CD8– interleukin [IL]-17+ T cells) and related cytokines IL-17, transforming growth factor-β (TGF-β), IL-10, IL-23, IL-6, and IL-22 were detected before and after cCRT. Correlations between alterations of circulating Th17 cells and treatment efficacy were analyzed. Kaplan-Meier analysis was used for overall survival (OS) and progression-free survival (PFS). Results: We found that 40 patients finished the entire cCRT schedule and met the endpoint of this study. The percentage of circulating Th17 cells in the LACC patients was higher than that in the controls, and it significantly decreased after cCRT ( P < 0.05). After cCRT, patients were divided into two groups based on the average of the Th17 cells declined. The subgroup of patients with a prominent decrease in circulating Th17 cells after cCRT had a higher treatment efficacy and longer PFS and OS times. Compared with the control patients, LACC patients had higher IL-6, IL-10, IL-22, TGF-β levels and a lower IL-23 level ( P < 0.05). After cCRT, IL-6, IL-10, IL-17, IL-23 level significantly increased and TGF-β level significantly decreased compared with the levels before cCRT ( P < 0.05). Conclusion: Circulating Th17 cells in the LACC patients (FIGO stage IIB–IIIB) were higher than those in the controls, but they generally decreased after cCRT. A more pronounced decrease in circulating Th17 cells after cCRT was correlated with better therapeutic effect and longer PFS and OS times.